Efforts to Improve the Quality of Handling Sharia Economic Disputes by Indonesian Religious Courts - Saut Maruli Tua Manik; Raihana; Yuniarti, Rahmi; Santoso , Mulia Akbar; Wilianli Melati Jaya Putri; Dhea Rahman Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The development of religious courts to address Sharia economic cases in Indonesia is considered a historic moment by many parties. However, efforts to improve the quality of resolving Sharia economic issues in religious courts have become increasingly important. This aims to enhance the trust of legal seekers, especially in Sharia economic disputes, towards dispute resolution through the alternative path faced through religious courts. The research was conducted using normative research methods and the analysis used was qualitative. The results show that religious courts in Indonesia have absolute jurisdiction in handling Sharia economic cases. Although the number of cases is increasing, the expansion of this authority challenges all elements of religious courts, including employees and judges. Despite the efforts of guidance carried out by the Supreme Court (Mahkamah Agung) in this case implemented by the Directorate General of Religious Courts, there are still several obstacles, such as the lack of harmony in laws related to Sharia economic matters. Then there are other factors influencing the quality of problem handling, namely the dualism of judicial institutions, namely Religious Courts as well as General Courts. The dualism of dispute resolution after the issuance of the Constitutional Court Decision Number 93/PUU-X/2012 remains a barrier, so the public has not fully been able to trust religious courts in the context of handling Sharia economic problems. Submission to the Consumer Dispute Settlement Board (BPSK) and agreements in contracts to use General Courts as a forum for resolving Sharia economic disputes reflect distrust in religious courts. Therefore, concrete steps are needed to overcome these barriers and increase public trust in religious courts to resolve Sharia economic problems.